Extinction Ratio and the Fiber Optic Transmission Networks (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
In the fiber optic communication network for example,- FTTH, EPON, NBN, OTN and so on, the most important components are fiber length between transmitter and receiver point. So, to make, cheap and meaningful communication through optical fiber it must be required to calculate how and what amount of signal is transmitted with the given length of the fiber. Finally, it is said that the optical fiber network have several limitations like extension ratio. So, it is necessary to investigate its affect on the performance of the Optical Network. This research is based on simulation by OptiSystem 0.17 on the basis of Dense wavelength division multiplex (DWDM) technology, Erbium Doped Fiber Amplifier (EDFA), dispersion Compensating Fiber (DCF) and single mode fiber of length 50–100 km.